Study on Magneto-rheological Damper Control of the Gear System Shafting Vibration - Wang Kai; He Lidong; Xing Jian; Hu Hangling (Jixie chuandong)
In order to solve the problem that gearbox vibration and noise are too large,aparallel shafts system bench with gears is established to simulate the gearbox.One self-designed magnetorheological damper is installed at each shaft.Different working conditions are set to study the influences at different operating current of dampers.The acceleration sensor is used to measure the gearbox vibration in experiments,the influence of magneto-rheological damper on gear transmission shafting vibration is studied from the gearbox body vibration.The results show that the damper can reduce the vibration of the gearbox body,and the decreasing amplitude is rising with the damper working current increases.The decline of the vertical vibration is up to 30%,and the decline of the horizontal vibration is up to 40%.Through the analysis of time and frequency domain waveform,it is found that the04 000 Hz frequency component of vibration can be reduced by using magneto-rheological damper,especially the vibration amplitude of lower 1000 Hz component can be reduced by 60%,the vibration amplitude of around 3000 Hz component can be reduced by 80%.Application of magneto-rheological damper can change current to adapt to different conditions by monitoring the gear box vibration damper,which can keep the vibration of the gearbox low.